1994
DOI: 10.1016/0741-5214(94)90232-1
|View full text |Cite
|
Sign up to set email alerts
|

Superficial femoral vein: A useful autogenous harvest site

Abstract: SFV harvest is well tolerated, even in the absence of ipsilateral saphenous vein. The magnitude of the operation is greater than saphenous vein harvest but yields a thick-walled vein of excellent diameter with many applications as an autogenous conduit, particularly where a large-diameter graft is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
2
20
0
1
Order By: Relevance
“…In all three of these cases, however, the vein was similarly harvested to the distal popliteal vein [ 4 ]. In contrast to this study Sladen et al reported on a series of 25 interventions involving SFV harvest performed primarily for critical ischemia [ 26 ]. With the exception of one case, they avoided vein harvest to below the knee.…”
Section: Harvest-related Morbidity In Superficial Femoral Vein Usementioning
confidence: 85%
See 2 more Smart Citations
“…In all three of these cases, however, the vein was similarly harvested to the distal popliteal vein [ 4 ]. In contrast to this study Sladen et al reported on a series of 25 interventions involving SFV harvest performed primarily for critical ischemia [ 26 ]. With the exception of one case, they avoided vein harvest to below the knee.…”
Section: Harvest-related Morbidity In Superficial Femoral Vein Usementioning
confidence: 85%
“…The author Dr. Neufang always removes venous valves as a matter of routine, not least to prevent possible clot formation or subsequent stenosis on the comparatively large and rigid valves. Venous valves are destroyed according to the Valentine technique using a retrograde Mills valvulotome, as with the GSV, by cutting the valvular leaflet [ 26 , 47 ]. As SFV valves can be relatively rigid, this type of valve destruction can be challenging in individual cases and may cause damage to the vein wall.…”
Section: Procedures For the Dissection And Harvest Of Superficial Femomentioning
confidence: 99%
See 1 more Smart Citation
“…Other alternatives for obtaining autogenous material, such as harvesting of the superficial femoral vein, involve more complex techniques and higher operative mortality. 10 With recent advances in cryobiology enabling preservation of living cells and tissues for a long period of time, and given the high rate of shortterm occlusions and poor results with cryopreserved homografts veins, 11-13 a renewed interest has developed in cryopreserved arterial homografts, resulting in the creation of arterial banks. Construction of long bypasses with cryopreserved arterial homografts is less traumatic and is a technically simple procedure for lower-limb revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Der autologe Venenbypass stellt zweifelsfrei das optimale Verfahren zur infragenualen und kruralen Rekonstruktion der arteriellen Strombahn dar [12,37], wobei der in-situ-Bypass sicher das eleganteste und am wenigsten traumatische Verfahren ist [29]. Die Offenheitsraten der VSM als Bypassgefa Èû sind jedoch mit anderen autologen Venen (Armvenen, VSP, V. femoralis) nicht erreichbar [7,13,31].…”
Section: Diskussionunclassified